Keanekaragaman Echinodermata Di Pantai Desa Pakowa Bunta Kecamatan Nuhon Kabupaten Banggai - Karim, Wahyudin Abdul; Anggo, Sulasmi; Ningrum, Ervina Kusuma; Lige, Firga Nabila (Jurnal Biologi Babasal, 2022)
Sulawesi has quite diverse marine biota with various kinds of habitats, one of which is members of the Echinodermata phylum. This research aims to determine the diversity of Echinoderms on the coast of Pakowa Bunta Village, Nuhon District, Banggai Regency. This research was conducted in October-December 2021. The research method used was a quantitative descriptive method. Perpendicular line transect sampling technique with a length of 60 meters. There are 1 transect line at each station and the distance between transects is 50 meters, perpendicular transect lines starting from the coastline of each transect line there are 4 plots consisting of 3 transect lines, and in one transect there are 4 plots with a size of 5x5 meters with a distance between plots of 10 meters. This sample collection was carried out once on each transect. Based on the results of data analysis from this research, it can be concluded that the diversity of echinoderms in Pakowa Bunta Village, Nuhon District, Banggai Regency is classified in the medium category with a value of 1.384. In each of them, station 1 has a diversity index of 1.0243 in the medium category, station 2 has a diversity index of 1.4368 in the medium category, and station 3 has a diversity index of 1.2845 in the medium category. This is because the ecosystem conditions in that place have begun to be disturbed.